Marked hyperandrogenicity in a 60-year-old woman. (4th September 2017) - Aljenaee, Khaled; Ali, Sulaiman; Cheah, Seong Keat; MacEneaney, Owen; Mulligan, Niall; Hickey, Neil; Tun, Tommy Kyaw; Sreenan, Seamus; McDermott, John H
Abstract : Markedly elevated androgen levels can lead to clinical virilization in females. Clinical features of virilization in a female patient, in association with biochemical hyperandrogenism, should prompt a search for an androgen-producing tumor, especially of ovarian or adrenal origin. We herein report the case of a 60-year-old woman of Pakistani origin who presented with the incidental finding of male pattern baldness and hirsutism. Her serum testosterone level was markedly elevated at 21 nmol/L (normal range: 0.4–1.7 nmol/L), while her DHEAS level was normal, indicating a likely ovarian source of her elevated testosterone. Subsequently, a CT abdomen-pelvis was performed, which revealed a bulky right ovary, confirmed on MRI of the pelvis as an enlarged right ovary, measuring 2.9 × 2.2 cm transaxially. A laparoscopic bilateral salpingo-oophorectomy was performed, and histopathological examination and immunohistochemistry confirmed the diagnosis of a Leydig cell tumor, a rare tumor accounting for 0.1% of ovarian tumors. Surgical resection led to normalization of testosterone levels. Learning points: Hirsutism in postmenopausal women should trigger suspicion of androgen-secreting tumor Extremely elevated testosterone level plus normal DHEAS level point toward ovarian source Leydig cell tumor is extremely rare cause of hyperandrogenicity